Advances in BIOMEDICAL DEVICES. - Su, Eileen Lee Ming, contributor; Ili Najaa Aimi Mohd. Nordin, 1989-, contributor; Lem, Tien Chai, 1980-, contributor; Mitra Mohd. Addi, contributor; Neo, Chin Chea, contributor; Nurfareha Amran, contributor; Puspa Inayat Khalid, 1966-, contributor; Rubita Sudirman, contributor; Yap, Ee Han, contributor; Su, Eileen Lee Ming, editor; Rubita Sudirman, editor; Fauzan Khairi Che Harun, contributor; et al. (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2015)
Includes bibliographical references and index :p.92